Sintesis dan Karakterisasi Plastik Ramah Lingkungan dari Nata de manihot - Mia Oktarina; Iryani Ahmad; Iswendi Thabrani (Jurnal Periodic Jurusan Kimia UNP, 2012)
Plastic is a materials which required in everyday. But its use generate various problem, especially if the plastic used as packer of food. Usage of plastic directly  can give negative impact to health. To overcome the negative impact done by effort one of them making of environment friendly plastic  from natural materials like nata de manihot. The aim of this research are syntesis  plastic sheet  from nata de manihot, knowing the  physical and morphology, and time relation with power of biodegradation. This research early with making of nata de manihot and nata de coco used as comparator.  Measured nata’s thickness, then in press so that form sheet of nata flimsy which still wet. After that, immersion during 14 day in gliserol with concentration variation of 1%, 2%, 3%, and pa. This sheet is dried in the oven at temperature ± 70,  so that yielded sheet of nata which in form of plastic sheet. Its Morphology is analysed by SEM ( Scanning Electron Microscope), its power of biodegradation  tested with burying in ground during 8 days, and each every 2 days measured by weight of  rest of plastic sheet. Pursuant to result of research obtained plastic sheet of nata which is soaked in gliserol at concentration 3% yielding more flexible and  more transparent compared to other concentration. Total biodegradation of plastic nata de manihot is over in 8 days.